Closing the cycle for the cut rose industry by the reuse of its organic wastes: A case study in Ecuador. (20th May 2019) - Idrovo-Novillo, J.; Gavilanes-Terán, I.; Veloz-Mayorga, N.; Erazo-Arrieta, R.; Paredes, C.
Abstract: The soil conditions and the yield and quality of Rosa sp. var. Freedom were determined following the incorporation into the soil of rose waste composts, with or without fertigation; the effects of these treatments were compared with those of non-stabilised chopped rose wastes + fertigation (FWF). The growing conditions were those of a commercial greenhouse. The use of the composts, alone or combined with fertigation, increased the available P and K contents of the soil with respect to FWF. However, only the compost + fertigation treatments improved, in general, the soil fertility regarding the organic matter (OM), nitrogen and available micronutrient concentrations, in comparison to FWF. When the composts were added alone, irrigation with alkaline water increased the soil pH and, in consequence, reduced the availability of micronutrients. Overall, the combined use of compost and fertigation increased the cut rose yield and quality relative to the application of compost alone and FWF. Principal component analysis indicated that the OM, available Cu, Mn and Zn and total N contents and the pH of the soil were the principal soil parameters determining the yield and quality of the roses. This analysis classified the treatments in three groups: the compost + fertigation treatments; the treatments with compost alone; and the FWF treatment. The compost + fertigation treatments gave the highest net income (average for these treatments = 80388.92 US dollars ha −1 ). Therefore, the compost + fertigation treatments were highly beneficial with regard to increasing soil fertility and cut rose yield, quality and profitability. Highlights: The use of rose waste composts combined with fertigation improved soil fertility. Compost + fertigation treatments were the most suitable for cut rose production. The highest net incomes were achieved with the compost + fertigation treatments.